ANALISIS IMPLEMENTASI TAKSONOMI SOLO DAN TAKSONOMI BLOOM DALAM MENINGKATKAN PEMAHAMAN STRUKTUR TAKSONOMI PENDIDIKAN PADA SISWA DI SDN RAWA BUAYA 07 DAN SDN CENGKARENG TIMUR 03 - Lilis Suwandari; Dwi Rahmat; Susilawati; Herawati; Iroh Masruroh (STKIP Subang, 2026)
The implementation of learning taxonomies plays an important role in improving students' cognitive development and learning quality in elementary schools. However, classroom learning practices are still predominantly oriented toward Bloom's Taxonomy, while the application of the Structure of the Observed Learning Outcome (SOLO) Taxonomy remains limited. This study aimed to analyze the implementation of SOLO Taxonomy and Bloom's Taxonomy in improving students' understanding of educational taxonomy structures at SDN Rawa Buaya 07 and SDN Cengkareng Timur 03. This study employed a qualitative descriptive approach. The research subjects consisted of principals, fourth- and fifth-grade teachers, and students. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that Bloom's Taxonomy has been systematically implemented in lesson planning, classroom instruction, and assessment practices. In contrast, the SOLO Taxonomy has not yet been explicitly integrated into the learning process due to teachers' limited understanding of its concepts and application. Nevertheless, several learning activities implicitly reflected SOLO levels, particularly at the multistructural and relational stages. The integration of Bloom's and SOLO Taxonomies provides a more comprehensive framework for designing learning activities and assessing students' depth of understanding. Therefore, strengthening teachers' competencies in implementing both taxonomies is essential to support meaningful learning and improve students' higher-order thinking skills in elementary education.